Research on the material properties of concrete in subway stations after in service for 50 years - Bin Zhang; Shaohui He; Jianfei Ma; Jiaxin He; Yiming Li; Jinlei Zheng (Scientific Reports)
Abstract During the subway operation phase, the performance of concrete materials in subway stations has experienced a series of transformations. This study meticulously investigated the macroscopic and microscopic characteristics of concrete within the Beijing subway structure after 50 years of service. In strict accordance with concrete testing standards, experimental data of 50-year-old concrete were systematically collected to comprehensively analyze the changes in compressive strength, tensile strength, elastic modulus, Poisson’s ratio, and bond strength relative to the initial design values. This paper not only detected the condition of concrete aggregates after 50 years of operation but also examined their microstructural states. Moreover, an in-depth study was conducted on the elemental composition and chemical properties of hydrated products in subway station concrete following long-term operation. By delving into the material properties of subway concrete during its long-term operational process, this research offers significant and valuable references for similar underground structures.